การวิจัยและพัฒนากระบวนการมีส่วนร่วมของผู้ปกครองในการปลูกฝังคุณธรรมจริยธรรมให้กับนักเรียนประถมศึกษาปีที่ 1 : การประยุกต์ใช้กระบวนการแผนที่ผลลัพธ์ - สุราณีย์ ปาจารย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research is a research and development of the participatory process of parent involvement in moral and virtue cultivating for first grade students: an application outcome mapping process. The objectives of the research were 1) to develop the participatory process of parent involvement in moral and virtue cultivating for first grade students using outcome mapping process, 2) to study the effect of participatory process of parent involvement in moral and virtue cultivating for first grade students using outcome mapping process. The research used the quality research approach, The research collected data by participant and non - participant, interviewing, focus group with an application outcome mapping process. The data were analyzed by content analysis, comparison and analytic induction. The research results were as follows; 1. The participatory process of parent involvement in moral and virtue cultivating for first grade students using an application outcome mapping process had 3 procedures 1) design the intentions with accompanies by aiming together and planning the purposes for the goals 2) following up and operating the strategy plan; starting the tasks and developing the framework direction planned 3) making the assessment, evaluation and improvement plans; planning processes for making an assessment frame with some goals such as ; how did the assessment be used for the advantage? , who did the assessment? 2. The effects from using the participatory process of parent involvement in moral and virtue cultivating for first grade students were that the students reacted the progress markers at the high level; 1) The students had the development in the sense of diligence, economization, and discipline 2) the students kept teacher as a good symbol 3) the students gave respect for adults. 4) the students were amicable for the other 5) the students did not violate the rules. 6) the students competed to do the goodness. In the level expected, the students reacted the progress at the middle level, there was only a progress marker that the students reacted at the low level; devoting for the share.